Implementasi Pembelajaran Al-Qur’an Hadits dengan Strategi Pembelajaran Aktif Inovatif Kreatif Efektif dan Menyenangkan dalam Pembentukan Karakter Peserta Didik MIN 4 Way Kanan - Nuraprilia. P, Iin Dwi; Syafe'i, Imam; Akmansyah, Muhammad (CV. Creative Tugu Pena, 2024)
Character education is a very important program implemented to strengthen the character of students. Elementary school education is strategic for character education. One of the subjects that supports the implementation of strengthening character education is the Qur'an and Hadith. Preliminary research shows that MIN 4 Way Kanan has implemented active, innovative, creative, effective and enjoyable learning strategies in the formation of student character in learning the Qur'an and Hadith through a scientific approach. This research method is qualitative descriptive. Data sources consist of primary and secondary data. Data collection techniques are non-participant observation, in-depth interviews, and documentation. Data analysis is data collection, data reduction, data presentation, conclusions and verification. And the test of data validity is triangulation of sources and techniques. The results of this study indicate that First, the implementation of Al-Qur'an Hadith learning with the PAIKEM strategy on character building of students at MIN 4 Way Kanan, in the planning, integrates the existence of learning objectives, lesson materials and teaching and learning activities which are arranged in the syllabus and RPP containing religious values, discipline, creativity, independence, environmental and social care, and responsibility. Second, the implementation of learning the Qur'an Hadith with the PAIKEM strategy towards the formation of students' character at MIN 4 Way Kanan, in the implementation of the integration of preliminary activities, core activities and closing activities containing religious values, discipline, creativity, independence, environmental and social care, and responsibility. However, in character formation it is still low due to the lack of understanding of students through the instillation of role models and learning from teachers. Third, the implementation of learning the Qur'an Hadith with the PAIKEM strategy towards the formation of students' character at MIN 4 Way Kanan, in the evaluation integrated with authentic assessments, namely the domain of attitude, the domain of knowledge, and the domain of skills containing religious values, discipline, creativity, independence, environmental and social care, and responsibility. In this study, the strengthening of character education in the implementation of PAI learning is still weak due to the lack of instillation of exemplary methods from teachers.